Function of alanine racemase in the physiological activity and cariogenicity of Streptococcus mutans - Liu, Shiyu (Sci Rep, 2018)
The enzyme alanine racemase (Alr) has been a new target for the development of antibacterial drugs based on the involvement of D-Ala in bacterial cell wall biosynthesis. Our previous study noted that Alr is essential for the growth and interspecies competitiveness of S. mutans, the major causative organism of dental caries. However, physiological activity and cariogenicity of S. mutans affected by Alr remains unknown. The current study examined the biofilm biomass, biofilm structure, extracellular polysaccharide (EPS) synthesis, glucosyltransferase (gtf) gene expression, acid production and acid tolerance in the alr-mutant strain. We found that biofilm formation, biofilm structure, and EPS synthesis was in a D-Ala dose-dependent manner. Biofilm structure was loose in alr-mutant group and the ratio of EPS/bacteria was also elevated. Additionally, the expression levels of multiple gtfs were up-regulated, and acid tolerance was decreased. We also established in vivo models of dental caries and found that the incidence and severity of the caries were decreased in the alr-mutant group in comparison to the parental S. mutans group. Our in vivo and in vitro experiments demonstrate that Alr is essential for the cariogenicity of S. mutans and that Alr might be a potential target for the prevention and treatment of caries.